A Pragmatic Analysis On Directive Utterances In Adventure Movie And Its Subtitling - Supriyeni, Anisa, Dra. Siti Zuhriah Ariatmi, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
This research aims at describing the variation of the language forms of directive utterances and its subtitling, describing the equivalence of the speaker‟s intentions of directive utterances and its subtitling, and describing the equivalence of the politeness patterns of directive utterances in the adventure movie and its subtitling. The type of this research is descriptive qualitative research which the writer uses documentation and observation method as the method of collecting data. The data of this research are films which contain directive utterances that are found in the data source that is Up and The Mysterious Island adventure movie manuscripts and its subtitling. The result of the research show that firstly, the language forms of directive utterances in adventure movie and its subtitling is declarative sentences which are translated into declarative and imperative sentence, interrogative sentences which are translated into interrogative, imperative, and declarative sentence, and imperative sentences which are translated into imperative and declarative sentence. Secondly, the speaker‟s intentions of directive utterances are commanding, requesting, suggesting, warning and prohibiting utterance. Thirdly, the politeness patterns of directive utterances are bald on record, positive politeness, negative politeness and off record strategy